DEVELOPMENT OF A FLOW-THROUGH SYSTEM FOR CLEANING AND DISSOLVING FORAMINIFERAL TESTS - Haley B.A.; Klinkhammer G.P. (My University, 2002)
A novel flow-through method for cleaning and dissolving foraminiferal shells is presented. Using automated chromatographic equipment, the system chemically removes contaminant phases from the shells. The cleaned calcite is then dissolved in a stream of weak acid for minor and trace element analyses. The system operates at elevated temperature (80 °C) and pressures (850-900 psi) and is extremely reproducible. This method has several advantages compared to traditional batch method cleaning done in centrifuge vials. The most important of these is that nothing is lost from the flow-through system, permitting complete monitoring of and greater insight into the effects of cleaning and dissolution. Development of this method revealed that it is necessary to remove two contaminant phases from the shells: an oxide coating phase that is rich in Mn, Cd, and Mg, and a refractory phase that is rich in Ba and the rare earth elements (REEs). This cleaning is accomplished through the use of basic hydroxylamine and basic diethylene triamine pentaacetic acid (DTPA) solutions, respectively. Time-resolved analysis (TRA) of shell dissolution demonstrates that Orbulina shells are composed of high-Sr and low-Sr calcite types. Other minor (e.g., Mg) and trace (e.g., Cd, REEs, Ba) elements show the same distribution during dissolution as Sr. In Orbulina shells, the high-Sr (high-Mg) calcite always dissolves first, similar to observations of natural dissolution in the ocean. Consequently, this flow-through system may provide a simple solution to dissolution problems in proxy work. Further, since flow-through can provide several measurements of elemental composition for each calcite type, the method allows for true statistical evaluation of homogeneity during growth of the shell. Most significantly, this flow-through method fully cleans calcite, and provides information about the calcite and contaminant phases and thus should prove to be valuable in advancing geochemical proxies as tools for paleoceanographic investigations.
Keywords: FORAMINIFERA; CALCITE; PALEOPROXY; ICP-MS; MG/CA; RARE EARTH ELEMENTS